Causes and Climatic Consequences of the Impact Winter at the Cretaceous‐Paleogene Boundary - Clay R. Tabor; Charles G. Bardeen; Bette L. Otto‐Bliesner; Rolando R. Garcia; Owen B. Toon (Geophysical Research Letters)
Abstract Prolonged periods of low light and cold temperatures at Earth's surface are hypothesized effects of the end‐Cretaceous asteroid impact. However, debate remains about the causes and consequences of this “impact winter.” We perform simulations of the Chicxulub impact with an Earth system model that can simulate the evolution of extreme aerosol loading to quantify the climatic responses to emissions (soot, sulfur, and dust) associated with the impact winter. We show that all impact winter emissions can drastically reduce surface temperature and precipitation. However, only soot emission from impact‐driven firestorms is capable of reducing light to below the photosynthetic threshold for many months. Therefore, our results suggest that widespread fires may have been necessary to produce the observed pattern of marine extinction across the Cretaceous‐Paleogene boundary. We identify polar coasts and the surrounding open oceans as regions likely to have experienced the least climatic, and biotic, disruption from the impact winter.